The Incidence of Non-Tuberculous Mycobacteria (NTM) in TB Culture Samples in a South Indian Sub-Population: A Laboratory-Based Study - Navidita Kangabam; Sneha S Hegadi; Divya C; Nethravathy V; KN Chidambara Murthy (Applied Microbiology: Theory ＆ Technology, 2025)
Non-Tuberculous Mycobacteria (NTM) are now considered globally evolved emerging pathogens, causing infections ranging from self-limiting asymptomatic to life-threatening infections affecting multiple major organs. Numerous directives have been implemented to treat NTM infections, but owing to their innate resistance, complexity, and resemblance to Mycobacterium Tuberculosis (MTB), the diagnosis and treatments have a high failure rate. The study was designed to estimate the incidence of MTB and NTM infection and identify the occurrence of NTM. In our study, a retrospective analysis of 6 years (January 2017 to December 2022) was done using laboratory data. All the samples received for Acid-Fast Bacilli (AFB) culture were included. Standard Auramine O and Ziehl Neelsen (ZN) staining, Lowenstein Jensen (LJ) medium, and an automated BacT Alert Mycobacteria Indicator Tube (MGIT) for inoculation. Differentiation between MTB and NTM was done using a TB antigen MPT64 rapid test kit. Anonymized data resulting from the generalization method was used for statistical analysis. Our study found that the incidence of NTM was 19.8% among the AFB-positive samples. The infection was found to be more common in males (60.6%) than in females (39.3%). The maximum number of samples received was sputum and BAL, indicating that the pulmonary infection was more than extra-pulmonary. The outcome is consistent with reports of pulmonary infections dominating worldwide. Our year-wise report shows that the cases of both MTB and NTM were found to be on the rising trend. Despite the low cases, it was noted that the number increased over time.